Aspects of ribonucleic acid estimation - Mobbs, Betty (The University of Edinburgh, 1960)
About twenty years ago, the foundation for the localization and quantitative cytochemical study of ribonucleic acid (RNA) was laid by Caspersson (1936) and Brachet (1942), using the natural absorption of ultra -violet radiation by the nucleic acids and their affinity for basic stains respectively. At the same time, Claude (1943) was devising a biochemical technique for the study of cell fractions isolated by differential centrifugation. The development of these techniques, augmented by the use of radioactive isotopes, has established beyond any doubt the importance of ANA in the biosynthesis of protein. It would be difficult to overestimate the contribution which the use of biochemical methods has made to our knowledge of the role of RNA in the cell, but, as with all techniques, they must be eployed with an awareness of their limitations. The tissues used are not usually homogeneous populations of cells: for instance, in the liver, an organ widely used for the investigation of protein synthesis, although parenchymal cells account for eighty -five per cent of the cytoplasmic volume, only fifty to sixty per cent of the total number of cells are parenchymal, the rest constituting connective tissue, blood cells, blood vessels, macrophages, etc. As Hogeboom and Schneider (1955) point out, even morphologically identical cells may differ in biochemical properties. The techniques used often involve homogenization of the tissue, followed by the separation of various fractions by ultra -centrifugation of the cell -free extract. During these procedures, there is a possibility of morphological and biochemical alteration of the fractions, and redistribution of material 2. from one fraction to another. There is also the possibility that two or more types of particle have the same sedimentation constant, but different biochemical compositions (Danielli 1953). It is therefore important to make morphological and biochemical checks whenever possible to ensure that these errors are kept to a minimum. However carefully used, biochemical methods, which deal with amounts of material of the order of l0 6gms. at the lower end of their range, are unable to solve certain problems of cellular metabolism, for instance, those concerned with the growth of the cell between divisions, or with the processes which take place during division or during differentiation. Some of these problems can be dealt with at a biochemical level using homogeneous population of cells, such as a culture of micro -organisms dividing synchronously; but perfect synchrony is difficult to obtain, and the methods by which even partial synchrony can be achieved (e.g. temperature shocks, variations in light intensity) are likely to upset the metabolism of the cell (Scherbaum, 1957a; Iwamura and Myers, 1959). Probably filtration techniques such as that used on Escherichia coli by Maruyama and Yamagita (1956) are more satisfactory, but are not applicable to all types of cell. For the type of problem mentioned above, then, quantitative cytochemical methods capable of dealing with amounts of material found in a single cell (i.e. of the order of 10-12gms.) have been developed. Cytochemical methods also suffer from some of the sources of error mentioned in connection with biochemical ones, such as the possibility of extraction and redistribution of material during fixation. In addition to these, there may be other sources of inaccuracy, some of which will be discussed in greater detail later. Before a quantitative cytochemical technique can be used with confidence, therefore, it is essential to check it against another accepted method, either a cytochemical or a biochemical one. It may be of interest to note some examples of such studies to illustrate this point, mostly in connection with the estimation of deoxyribonucleic acid (DNA) rather than that of RNA. In 1950, Ris and Nirsky put forward evidence demonstrating that, provided certain conditions are fulfilled, it is permissible to use the intensity of Feulgen staining as a measure of the amount of DNA in the nucleus. They showed this by the U e of model systems and by comparing the amounts of stain in erythrocyte and liver nuclei of various vertebrates with values obtained biochemically on a known number of nuclei. Provided the degree of ploidy was taken into account they found good agreement between the biochemical and the cytochemical results. A similar investigation was carried out by Leuchtenberger et al. (1951) on mammalian liver, spleen, and kidney. These authors also obtained good agreement between the amount of DNA in isolated nuclei as estimated by C.aspersson's method of ultra-violet microspectrophoto - metry a_,d by biochemical methods (Leuchtenberger et al., 1952,a & b). Ultra-violet absorption methods were used by Walker and Yates (1952 a and b) in a study comparing the DNA values obtained for several types of erythrocytes and sperm with the corresponding values found by other authors using biochemical techniques. Using tissue culture cells which had been filmed when living, Walker and Yates extended their investigation to include actively growing and dividing cells. They measured the ultra -violet absorption of the nuclei at known points in the life -cycle of the cells and compared the values obtained with the intensity of Feulgen stain in the same nuclei. Both methods showed that there is a gradual increase of material during interphase, but there was a discrepancy in the rates of this increase obtained by the two techniques. Since the Feulgen staining of cells is generally considered specific for DNA, whereas ultra -violet absorption at the wavelength used is specific for certain types of bonds found in all purines and pyrimidines, the discrepancy between the ultra-violet and the Feulgen data may be accounted for by the presence of DNA precursors in the living nuclei. Firket (1953) also studied the synthesis of DNA during the growth of tissue culture cells, using Feulgen staining and an autora bgraphic method (the incorporation of tritium -labelled thymidine into DNA) and, like Walker and Yates, found that synthesis occurred during interphase. The investigation of nucleoprotein changes in a bacterially induced plant tumour by Rasch et al. (1959) demonstrates how cytochemical and biochemical methods may complement each other. Estimated biochemically, RNA values showed scarcely significant differences between the stems forming tumours and the control stems, whereas the cytochemical method used (cytophotometry after Azure B staining) made obvious localized increases in RNA content involving comparatively few cells. These increases had been masked by the inclusion of large numbers of normal cells for the biochemical analysis. Conversely, during the first few days of tumour growth, the large increase in DNA content found by biochemical methods was absent when DNA was measured by the Feulgen technique. The authors suggest that the 'extra' DNA may represent a labile component which is lost from the cells during the cytochemical procedures, or that it is distributed uniformly throughout the host tissue and that thetefore the increase per cell is too slight to be detected photometrically, or that contamination has occurred during the biochemical procedure. The use of an autoradiographic method would perhaps help to elucidate this point. An example of the checking of one cytochemical method of measurement against another is given by Mendelsohn and Richards (1958), who measured the intensity of gallocyanin- chrome alum stain in the same ascites tumour cells by scanning microphotometry and by the two wavelength method. They obtained a high degree of proportionality in the results. The importance of using living cells whenever possible is illustrated by the wor'. of King (1959) , who compared the nucleic acid and protein content of the cytoplasm of ascites tumour cells determined by ultra- violet absorption methods with the dry mass obtained by interference microscopy. He found good agreement between the two determinations in fresh cells, but the results from fixed cells were more variable. Some of the above investigations were facilitated by the fact that, with certain reservations, e.g. in the case of aneuploid or polyploid cells, all the non- dividing somatic cells of an animal contain virtually the same amount of DNA, the diploid amount, while normal mature sperm contain the haploid amount of DNA. Such cells as nucleated erythrocytes and sperm can therefore be used as standardsn the comparison of techniques and to check reliability. In the case of RNA, however, there are no such standards. Even in cultures of micro -organisms and protozoa, there seems to be quite a large biological variation between the individual cells at any particular stage in the life -cycle (Brachet, 1957; I=iitchison and Walker, 1959) . This is an important reason for the scarcity of cytochemical mehods for the quantitative investigation of RNA compared with the number of methods for its detection. It is also more unstable than DNA and exists in several different fractions within the cell, which may require different techniques for their investigation. The first part of this dissertation consists of a brief review of the cytochemical methods available for the estimation of RNA, together with results I have obtained using some of these methods, and the conclusions to be drawn from them. The second part is a description of the organization of RNA within the cell, with reference to the cytochemical techniques which have been used for its investigation, foTbwed by the record of an attempt to devise a technique at a biochemical level which could be adapted for use on a cytochemical level for the extraction of one RNA fraction from intact cells.